Droughts in East Africa: Causes, impacts and resilience - Gebremeskel Haile, Gebremedhin; Tang, Qiuhong; Sun, Siao; Huang, Zhongwei; Zhang, Xuejun; Liu, Xingcai (Earth-science reviews, 2019)
East Africa (EA) has been the primary focus for various drought studies in recent years. However, a comprehensive analysis of droughts, including their evolution, complexity, social implications and people's vulnerability is currently lacking. Hence, there is a pressing need for an overview of drought studies in EA. Here, we present a state-of-the-art review of the causes and impacts of, and resilience to droughts in EA. Studies reveal that droughts tend to be more frequent, longer and more severe in the boreal spring and summer in EA, as the overall precipitation and water storage abruptly decline. A decrease in drought frequency is observed during the boreal autumn season (October–November). As these studies have only been analysed within the context of sparse and short-term regional climate data with very complex spatial and seasonal climate patterns, they are subject to uncertainties. The main causes for the changing pattern of droughts include climate variabilities and anthropogenic effects. Droughts have extensive impacts on human beings, environment, water resources and agriculture. Environmental rehabilitation involving the development of ecosystem services, biodiversity enhancement and soil and water conservation is found to be a suitable strategy to adapt to drought conditions. A better understanding of the causes and impacts of droughts, participatory management and community level actions are essential for building resilience to drought. Strong citizens–government–stakeholder cooperation is also valuable in monitoring and managing drought. The knowledge and insights gained from this review will help the countries in EA to build a drought-resilient society and will form a basis of information for other regions outside of EA.